Emotional relevance and prejudice: testing the differentiated effect of incidental disgust on prejudice towards ethnic minorities - Pascal, Emilia; Holman, Andrei Corneliu; Miluț, Felicia Mihaela (Frontiers in Psychology, 2023)
Negative emotions such as disgust or anger influence the evaluation of minorities and amplify prejudice, stereotypes, and discrimination behaviors towards them. However, new discoveries suggest that these spillover effects might be more specific in the sense that the bias might occur only if the emotions are specific to the affect that is generally evoked by that particular minority, i.e. anger increases prejudice towards anger-relevant groups, and disgust towards disgust-relevant groups. Our study aimed to examine, the specificity of the spillover effects, namely the importance of emotion’s relevance to the prejudice towards out-groups. To test this hypothesis, we investigated the influence of incidental disgust on the evaluation of two minorities, one that is usually associated with disgust (the Roma minority) and one usually associated with anger (the Hungarian minority). We used a 2 × 2 between-subjects experimental design where we manipulated the emotion experienced by the participants (disgust versus neutral) and the target they evaluated (Romani or Hungarian minority). We tested the effects of these manipulations on three aspects of prejudice toward the target group: cognitive, affective, and behavioral. The results support the specificity of the spillover effect, by showing that incidental disgust increased prejudice only towards the disgust-relevant target, namely the Roma minority, and that the intensity of this emotion experienced by the participants mediates this effect. Moreover, incidental disgust increased not only the negative emotions associated with the Romani (i.e., the affective component) but also the negative cognitions associated with them and the desire to maintain an increased social distance (i.e., behavioral prejudice). These findings highlight the importance of emotions’ relevance in bias toward minorities and provide a starting point for future anti-discrimination interventions.